Updates and advances in etiopathogenesis of tumors of the temporomandibular joint (Research, Society and Development, 2020)
Introduction: Tumors and pseudotumors that affect the temporomandibular joint (TMJ) tend to be frequent and their symptoms are very similar to the several disorders that affect the joint, such as: pain, limited mouth opening and occlusal changes. Objective: The aims of this study were to evaluate the main aspects related to etiopathogenesis, the modalities of diagnosis and treatment of the main tumors and pseudotumors that affect the TMJ, through a review of the current literature. Methods: a search was performed on databases indexed on Google Scholar and Medline using the following meshes: Temporomandibular joint; temporomandibular joint disorders; neoplasms; Bone neoplasms and orthognathic surgical procedures. Results & discussion: studies on etiopathogenesis, diagnostic modalities and aspects related to the treatment of the main tumors that affect TMJ were found, such as osteochondroma, synovial chondromatosis, tenosynovial giant cell tumor, osteomas, chondromas and chondroblatomas, in addition to malignant varieties, as osteossarcoma and chondrosarcoma. Final considerations: the complementary exams are essential for the differential diagnosis of these pathologies, given the non-specificity of the symptoms normally associated. In addition, they are important to evolution of the lesions and the surgical planning that involves most cases. When necessary, surgical resection of these tumors is associated with joint reconstruction and correction of dental-facial deformity, favoring better joint function, reducing symptoms, improving aesthetics and restoring quality of life to the affected patients.